Differential Influence of Same‐ and Cross‐Ethnic Friends on Ethnic‐Racial Identity Development in Early Adolescence. Issue 3 (30th March 2019) - Jugert, Philipp; Leszczensky, Lars; Pink, Sebastian
Abstract : Recent research has shown that peers influence ethnic‐racial identity (ERI) development during early adolescence. Arguments based on social identity theory, however, suggest that only same‐ethnic but not cross‐ethnic friends are important for ERI development. Using longitudinal social network analysis, we examined peer influence of both same‐ and cross‐ethnic friends on ERI attachment and private regard. Data were drawn from six ethnically diverse schools in Western Germany ( N = 1, 349; M age = 13.3). Our results provide empirical evidence for early adolescents' ERI being influenced by same‐ but less by cross‐ethnic friends. Considering peers' ethnicity therefore is crucial for understanding peer influence on ERI development.